High-altitude meteors detected by the interferometric MU radar - Kastinen, Daniel; Kero, Johan (Monthly Notices of the Royal Astronomical Society, 2022)
ABSTRACT We have re-analysed part of the middle and upper atmosphere (MU) radar meteor head echo data set collected during 2009–2010 and confirmed the existence of a rare high-altitude radar meteor population reaching up to ∼150 km altitude. The number of detections decreases significantly as a function of initial altitude. Out of the total amount of 106 000 events, 74 had an initial altitude >130 km while four of those had an initial altitude >145 km. High-altitude radar meteor observations have been reported before, e.g. using the EISCAT VHF radar and the Jicamarca Radio Observatory. The main novelty of this study is that the observations were performed using methods that render the final data set unambiguous in direction of arrival together with rigorously tested analysis routines that were validated by noisy raw data simulations. Due to our experimental set-up the maximum detectable range was limited to 148 km. Hence, we cannot confirm or deny the existence of radar meteors above that altitude.